X-ray observations of medium Z H- and He-like ions with satellites from C-Mod tokamak plasmas. (28th May 2015) - Rice, J E; Reinke, M L; Ashbourn, J M A; Gao, C; Bitter, M; Delgado-Aparicio, L; Hill, K; Howard, N T; Hughes, J W; Safronova, U I
Abstract: X-ray spectra of H- and He-like ions (and satellites) from argon, calcium and chlorine have been measured in Alcator C-Mod tokamak plasmas using a high wavelength resolution imaging x-ray spectrometer system. For H-like charge states, the Ly α doublet intensity ratio is found to be slightly greater than 1/2 due to interaction with the 2 S1/2 fine structure sub-level. Neighbouring satellites with spectator electrons occupying n = 2 through n = 7 have been modelled. The Ly α doublet ratio scalings with electron density and temperature are shown to be in good agreement with collisional–radiative modelling. For He-like ions, the n = 2 satellite intensities are in good agreement with calculations and can be used to determine the electron temperature. The high n Rydberg series has been resolved up to 1s 2 –1s14p, and satellites with spectator electrons up to the n = 12 level have been identified.